PRE-AND POST-TREATMENT INDICATIONS IN CHRONIC HEART FAILURE WITH VARIOUS COMORBID DISEASES - Erkinova Nigora Erkinovna (Galaxy International Interdisciplinary Research Journal, 2022)
120 patients with SYuE under observation were divided into three groups based on their comorbid diseases, all patients received 25-50 mg of the standard treatment of SYuE, β-blockers, azilsartan as an angiotensin II receptor antagonist, and eplerenone, the last generation of MKRA, as an antifibrotic agent. Six-minute walk test, clinical status rating scale, and Minnesota Questionnaire scores were analyzed before and after treatment in chronic heart failure with various comorbidities.